Catalytic Combustion of Low Concentration Methane over Catalysts Prepared from Co/Mg-Mn Layered Double Hydroxides - Hongfeng Liu; Xingrui Fu; Xiaole Weng; Yue Liu; Haiqiang Wang; Zhongbiao Wu (Journal of Chemistry)
A series of Co/Mg-Mn mixed oxides were synthesized through thermal decomposition of layered double hydroxides (LDHs) precursors. The resulted catalysts were then subjected for catalytic combustion of methane. Experimental results revealed that the Co4.5Mg1.5Mn2LDO catalyst possessed the best performance with the T90=485°C. After being analyzed via XRD, BET-BJH, SEM, H2-TPR, and XPS techniques, it was observed that the addition of cobalt had significantly improved the redox ability of the catalysts whilst certain amount of magnesium was essential to guarantee the catalytic activity. The presence of Mg was helpful to enhance the oxygen mobility and, meanwhile, improved the dispersion of Co and Mn oxides, preventing the surface area loss after calcination.